The Effectiveness of the Remap STAD Learning Model on Empowering Creative Thinking Skills - Irawan, Ferry; Zakiyah R, Nur; Hanip, Rival (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
One of the 21st century thinking skills is creative thinking skills. Students as prospective educators are required to learn and develop self-actualization in solving problems scientifically. This study aims to determine the effectiveness of Remap STAD learning models towards the empowerment of students' creative thinking skills. This research is a quasy experimental study and uses a Non equivalent pretest-posttest control group design. The population is all students of class XI IPA SMAN 4 Malang, totaling 234 students. A sample of 102 students was selected based on the equality test to determine the experimental class, positive control, and negative control. The instrument used used essay tests in accordance with indicators of creative thinking skills and the results were analyzed using the one-way anacova test. The results showed that the Remap STAD learning model effectively empowers students' creative thinking skills. The implication of the research conducted is to train students to think metaphorically to produce unique ideas or concepts as a form of achieving creative thinking skills. It is recommended that educators integrate the Remap STAD model in biology learning to foster student engagement and stimulate higher-order thinking processes necessary for solving contextual problems in daily life.